Reliability and validity of the Colombian version of the Revised Sociosexual Orientation Inventory - Romero, D. (2022)
Sociosexuality refers to an individual’s disposition to have casual sex without establishing affective bonds and has been widely studied worldwide using the Revised Sociosexual Orientation Inventory (SOI-R; Penke & Asendorpf, 2008). Despite its many validations in different cultural contexts, no psychometric analyses of this instrument have been conducted in Spanish-speaking Latin American countries. To address this gap in the literature, we examined the psychometric properties of the SOI-R in Colombia. In a cross-sectional study with a large sample of participants (N = 812; 64% women), we conducted exploratory and confirmatory factor analyses to identify different factor structures and determine which had the best fit for our sample and examined the reliability of the scale. Results showed that a three-factor structure, with sociosexual behaviors, attitudes, and desire as first-order factors, and global sociosexuality as a second-order factor, had the best fit indexes. Each factor presented good reliability indexes. Replicating already established gender differences, we also found that men scored higher on each factor when compared to women. These findings show that the SOI-R is a reliable and valid instrument to assess sociosexuality in countries where sociosexuality research is underrepresented.